A paradigm for the development of knowledge-intensive enterprises: the case of agricultural knowledge-intensive enterprises in west of Iran. (31st March 2023) - Jamshidnezhad, Gelareh; Vahedi, Marjan; Poursaeed, Alireza; Chaharsoughi-Amin, Hamed
The present research aimed to qualitatively design a paradigm for the development of agricultural knowledge-intensive enterprises in the west of Iran using grounded theory. The research population was composed of chief executive officers (CEOs) of agricultural knowledge-intensive enterprises. Based on the results; the causal conditions are composed of the components of aspirations, scientific mission, policy-legal factors, cultural factors, and self-esteem. The contextual conditions are composed of the components of governmental support, team making, and economic factors. The core category includes gaining competitive advantage and adaptability, and the intervening conditions include personal factors, wisdom-orientation, the existence of R&D culture, and corporate features. The components constituting strategies are managerial and policymaking factors, educational and research activities, platforms and infrastructure, scientific communications and networks, knowledge dissemination, and entrepreneurship. Finally, the development of knowledge-intensive enterprises will have positive consequences from the perspective of science, economy, and the realisation of Iran's 20-Year Vision Document, human, production, and marketing.